Cocculina delphinicula sp. nov., a new cocculinid species from whale bone in the East China Sea (Gastropoda: Cocculiniformia) - Zhang, Shuqian; Zhang, Suping (Zootaxa, 2018)
A new cocculinid species collected from a dolphin skull in the East China Sea is described and assigned to the genus Cocculina Dall, 1882. This new species, Cocculina delphinicula sp. nov., has a medium sized, depressed shell sculptured with regularly spaced concentric growth lines and fine radial threads. The radula has a formula of (ca. 20)+5+1+5+(ca. 20) with a vestigial rachidian, lateral 1 weak but well defined, having an outline that frequently terminates into a small beak-like cusp, laterals 2 and 3 with 3–4 cusps, lateral 4 with a large primary cusp and an outer secondary cusp.